Detection of specific gene rearrangements by fluorescence in situ hybridization in 16 cases of clear cell sarcoma of soft tissue and 6 cases of clear cell sarcoma-like gastrointestinal tumor - Keiko Segawa; Shintaro Sugita; Tomoyuki Aoyama; Terufumi Kubo; Hiroko Asanuma; Taro Sugawara; Yumika Ito; Mitsuhiro Tsujiwaki; Hiromi Fujita; Makoto Emori; Tadashi Hasegawa (Diagnostic Pathology, 2018)
Abstract Background Clear cell sarcoma of soft tissue (CCSST) and clear cell sarcoma-like gastrointestinal tumor (CCSLGT) are malignant mesenchymal tumors that share some pathological features, but they also have several different characteristics. They are well known to express chimeric fusions of Ewing sarcoma breakpoint region 1 (EWSR1) and cAMP response element-binding protein (CREB) family members; namely, EWSR1-activating transcription factor 1 (ATF1) and EWSR1-CREB1. In addition, recent studies have suggested the presence of other fusions. Methods We used fluorescence in situ hybridization to detect specific rearrangements including EWSR1, ATF1, CREB1, and cAMP response element modulator (CREM) in 16 CCSST and 6 CCSLGT cases. We also used reverse transcription polymerase chain reaction (RT-PCR) to detect specific chimeric fusions of EWSR1-ATF1 and EWSR1-CREB1 using fresh tumor samples in available cases. Results A total of 15 of 16 CCSST cases (93.8%) had EWSR1 rearrangement, of which 11 (68.8%) also had ATF1 rearrangement, suggestive of the presence of EWSR1-ATF1 fusions. One CCSST case (6.3%) was found to have EWSR1 and CREM rearrangements, and 4 of 6 CCSLGT cases (66.7%) had EWSR1 rearrangement, of which 2 (33.3%) showed ATF1 rearrangement and the other 2 cases (33.3%) showed CREB1 rearrangement. These cases most likely had EWSR1-ATF1 and EWSR1-CREB1 fusions, respectively. RT-PCR was performed in 8 available cases, including 6 CCSSTs and 2 CCSLGTs. All CCSSTs showed EWSR1-ATF1 fusions. Among the 2 CCSLGT cases, one had EWSR1-ATF1 fusion and the other had EWSR1-CREB1 fusion. Conclusions Rearrangements of EWSR1 and ATF1 or EWSR1-ATF1 fusion were predominantly found in CCSST, whereas those of EWSR1 and CREB1 or EWSR1-CREB1 tended to be detected in CCSLGT. A novel CREM fusion was also detected in a few cases of CCSST and CCSLGT. The cases in which EWSR1 rearrangement was detected without definitive partner genes should be considered for the presence of CREM rearrangement.